2015
DOI: 10.1104/pp.15.00992
|View full text |Cite
|
Sign up to set email alerts
|

9-Lipoxygenase-derived oxylipins activate brassinosteroid signaling to promote cell wall-based defense and limit pathogen infection

Abstract: The oxylipins, a large family of oxygenated lipid derivatives, regulate plant development and immunity. Two members of the 9-lipoxygenase (9-LOX) oxylipin pathway, 9-hydroxyoctadecatrienoic acid and 9-ketooctadecatrienoic acid, control root development and plant defense. Studies in Arabidopsis (Arabidopsis thaliana) using a series of 9-hydroxyoctadecatrienoic acidand 9-ketooctadecatrienoic acid-insensitive nonresponding to oxylipins (noxy) mutants showed the importance of the cell wall as a 9-LOX-induced defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 62 publications
1
56
0
Order By: Relevance
“…Moreover, OPDA confers resistance of Arabidopsis plants against different pathogens in the absence of JA/JA-Ile [8,13], while rice mutants deficient in OPDA showed altered defense against the blast fungus Magnaporthe oryzae [14]. Recent studies have also suggested that OPDA is involved in enhancing callose accumulation in host plants to limit pathogen infection [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, OPDA confers resistance of Arabidopsis plants against different pathogens in the absence of JA/JA-Ile [8,13], while rice mutants deficient in OPDA showed altered defense against the blast fungus Magnaporthe oryzae [14]. Recent studies have also suggested that OPDA is involved in enhancing callose accumulation in host plants to limit pathogen infection [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented the importance of the 9-LOX pathway in regulation of lateral root development and activating defence against virulent Pseudomonas and pest attack (Hwang & Hwang, 2010;López et al, 2011;Montillet et al, 2013;Nalam, Keeretaweep, Sarowar, & Shah, 2012;Vellosillo et al, 2007;Vicente et al, 2012). Studies using nonresponding to oxylipins (noxy) mutants, which have an impaired 9-LOX signalling pathway, also showed the relevance of the cell wall and mitochondria as components of 9-LOXinduced defence (Marcos et al, 2015;Vellosillo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, insects release salivary secretions while feeding, which could potentially activate wound-induced signaling molecules, such as OPDA, and trigger the downstream defenses in plants (Park et al, 2013;Bosch et al, 2014aBosch et al, , 2014bGuo et al, 2014;López-Galiano et al, 2017). More recent studies have suggested that oxylipins, a large family of oxidized lipids including OPDA, are involved in enhancing callose accumulation in host plants to limit pathogen infection (Marcos et al, 2015;Scalschi et al, 2015), which is also a potential defense mechanism utilized by plants to disrupt aphid colonization.…”
mentioning
confidence: 98%